The effect of measles immunization booklet (BOKSICAM) on mothers' knowledge about measles immunization - Ita Susanti; Asmima Yanti (Institute Of Computer Science (IOCS), 2025)
One of the contributors to the high child mortality rate is measles. The easy transmission of the measles virus has caused a very significant increase in measles cases. The government has implemented a measles immunization program as an effective prevention effort so that this case does not spread quickly so that transmission can be stopped, but the community still considers this case trivial and will heal on its own without any treatment. Therefore, effective health education efforts are needed with booklet media to increase public knowledge about measles immunization. The purpose of this study was to determine the effect of measles immunization booklet media (BOKSICAM) on mothers' knowledge about measles immunization. The study was conducted at one of the Integrated Health Service Posts in the Drien Jalo Health Center working area in December 2024. This study is a Quasi Experimental type, with a one group pre-post test design. The number of samples was 46 respondents with a sampling technique of total sampling. The results of the study showed an increase in maternal knowledge after being given health education using BOKSICAM media. The results of the paired t-test analysis obtained a p value = 0.000 <?=0.05, which means that there is an influence of the measles immunization booklet (BOKSICAM) on mothers' knowledge of measles immunization at the Drien Jalo Health Center. By increasing mothers' knowledge of measles immunization, it is expected that the coverage of measles immunization at the Drien Jalo Health Center can increase.